Apomorphine subcutaneous infusion in patients with Parkinson's disease with persistent motor fluctuations (TOLEDO): a multicentre, double-blind, randomised, placebo-controlled trial. Issue 9 (September 2018) - Katzenschlager, Regina; Poewe, Werner; Rascol, Olivier; Trenkwalder, Claudia; Deuschl, Günther; Chaudhuri, K Ray; Henriksen, Tove; van Laar, Teus; Spivey, Kevin; Vel, Senthil; Staines, Harry; Lees, Andrew
Summary: Background: Subcutaneous apomorphine infusion is a clinically established therapy for patients with Parkinson's disease with motor fluctuations not optimally controlled by oral medication. Open-label studies have shown that apomorphine infusion is effective in reducing off time (periods when antiparkinsonian drugs have no effect), dyskinesias, and levodopa dose, but confirmatory evidence from double-blind, controlled studies is lacking. We aimed to investigate the efficacy and safety of apomorphine infusion compared with placebo in patients with Parkinson's disease with persistent motor fluctuations despite optimised oral or transdermal treatment. Methods: In this randomised, placebo-controlled, double-blind, multicentre trial, we enrolled patients at 23 European hospitals who had been diagnosed with Parkinson's disease more than 3 years previously and had motor fluctuations not adequately controlled by medical treatment. Patients were randomly assigned (1:1) with a computer-generated randomisation code, stratified by site, to receive 3–8 mg/h apomorphine or placebo saline infusion during waking hours (16 h a day [range 14–18 was acceptable]) for 12 weeks. The flow rate of the study drug and other oral medications could be adjusted during the first 4 weeks on the basis of individual efficacy and tolerability, after which patients entered an 8-week maintenance period. The primary endpoint was the absolute change in daily off time based on patient's diaries, and was assessed in the full analysis set, which was defined as all patients who received at least one dose of allocated study drug and had efficacy data available at any timepoint post-baseline. Safety was assessed in all patients who received at least one dose of apomorphine or placebo. All study participants and investigators were masked to treatment assignment. Both the 12-week double-blind phase and the 52-week open-label phase of this study are now complete; this paper reports results for the double-blind phase only. This study is registered with ClinicalTrials.gov (NCT02006121 ). Findings: Between March 3, 2014, and March 1, 2016, 128 patients were screened for eligibility and 107 were randomly assigned, of whom 106 were included in the full analysis set (n=53 in both groups). Apomorphine infusion (mean final dose 4·68 mg/h [SD 1·50]) significantly reduced off time compared with placebo (−2·47 h per day [SD 3·70] in the apomorphine group vs −0·58 h per day [2·80] in the placebo group; difference −1·89 h per day, 95% CI −3·16 to −0·62; p=0·0025). Apomorphine was well tolerated without any unexpected safety signals. Six patients in the apomorphine group withdrew from the study because of treatment-related adverse events. Interpretation: Apomorphine infusion results in a clinically meaningful reduction in off time in patients with Parkinson's disease with persistent motor fluctuations despite optimised oral or transdermal therapy. Funding: Britannia Pharmaceuticals.